The digital arms trade. (Economist, 2013)
The article considers the marketing of exploits, computer software which allows computer hackers to access computers through design flaws in their operating systems. An increase in the illegal development and sale of exploits is considered. The computer software industry firm Netragard is used as an example of legal sales of exploits to business enterprises and government agencies. Use of exploits by intelligence services is examined.